2005
DOI: 10.1177/0748730405279174
|View full text |Cite
|
Sign up to set email alerts
|

Shortened Seasonal Photoperiodic Cycles Accelerate Aging of the Diurnal and Circadian Locomotor Activity Rhythms in a Primate

Abstract: The gray mouse lemur (Microcebus murinus), a prosimian primate, exhibits seasonal rhythms strictly controlled by photoperiodic variations. Previous studies indicated that longevity can be altered by long-term acceleration of seasonal rhythms, providing a model for assessing various aspects of aging. To assess the effect of aging and accelerated aging on the circadian system of this primate, we compared the circadian rhythm of the locomotor activity in adult mouse lemurs (2-4.5 years, n = 9), aged mouse lemurs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(58 citation statements)
references
References 37 publications
4
53
0
1
Order By: Relevance
“…Moreover, a recent study demonstrated that thermoregulation differed according to photoperiod and age in this species , see comments in (Van Someren, 2007). Several of these studies indicate that daily and seasonal biological rhythms are altered in old mouse lemurs in ways that are remarkably similar to what is observed in human aging (Huang et al, 2002;Cayetanot et al, 2005): a decrease in amplitude of the locomotor activity level, an increased activity during the resting diurnal phase and an increase in fragmentation. For these and other reasons, the mouse lemur can be regarded as a model of primary importance for human aging (Bons et al, 2006).…”
Section: Introductionmentioning
confidence: 87%
“…Moreover, a recent study demonstrated that thermoregulation differed according to photoperiod and age in this species , see comments in (Van Someren, 2007). Several of these studies indicate that daily and seasonal biological rhythms are altered in old mouse lemurs in ways that are remarkably similar to what is observed in human aging (Huang et al, 2002;Cayetanot et al, 2005): a decrease in amplitude of the locomotor activity level, an increased activity during the resting diurnal phase and an increase in fragmentation. For these and other reasons, the mouse lemur can be regarded as a model of primary importance for human aging (Bons et al, 2006).…”
Section: Introductionmentioning
confidence: 87%
“…Chez le microcèbe âgé (âge > 5 ans), l'activité locomotrice, strictement nocturne chez l'adulte, survient en avance de phase, se fragmente et des séquences d'activité sont présen-tes pendant le repos diurne (Figure 3). La resynchronisation des rythmes journaliers lors d'avance ou de retard de phase est également modifiée [13]. En outre, les résultats révèlent un dysfonctionnement des répon-ses à l'entraînement photopériodique, phénomène rarement mentionné dans les études sur le vieillissement des rythmes d'activité.…”
Section: Vieillissement Et Rythme D'activité Généraleunclassified
“…Their maximum life expectancy of about 8 years in the wild and up to 18.5 years in captivity (Weigl and Jones, 2005) is much shorter than for other nonhuman primates (Weigl and Jones, 2005;Zimmermann and Radespiel, 2015). Consequently, mouse lemurs represent an important animal model for aging (Perret, 1997;Cayetanot et al, 2005;Languille et al, 2012;Zimmermann and Radespiel, 2014;Zimmermann et al, 2016) and biomedical research, e.g. on Alzheimer's disease (Austad and Fischer, 2011;Verdier et al, 2015).…”
Section: Introductionmentioning
confidence: 99%